Who Are The Jesuits, And What Is Their Role In World History? - Caleb Kimball (Smashwords Edition, 2014)
Who are the Jesuits, what is their history, and what is their purpose? How did the Jesuits influence the Counter Reformation? What role did the Jesuits play in the translation of the King James Bible? What was the Jesuits' part with the other versions and translations of the Bible? Did the Jesuits have anything to do with the assassinations of Presidents Lincoln, Kennedy, and Harrison? This book answers all of those questions and more, and attempts to uncover the real reason that the Jesuits were formed, their mission, and what they have done and are doing to accomplish that mission. The answer to these questions are more controversial that you may think.